Surgical Antimicrobial Prophylaxis Among Pediatric Patients in South Africa Comparing Two Healthcare Settings. Issue 2 (February 2019) - van der Sandt, Nicolene; Schellack, Natalie; Mabope, Lindi A.; Mawela, Mothahadini P.B.; Kruger, Danie; Godman, Brian
Abstract : Background: Appropriate use of surgical antimicrobial prophylaxis (SAP) is a concern in view of its impact on morbidity, mortality and costs. Little is currently known about SAP in South Africa. Objective: To assess compliance to SAP guidelines for pediatric patients undergoing surgery in 1 of 4 surgical subspecialties among hospitals in South Africa. Methods: An eight-month retrospective chart review in both a teaching hospital and a private hospital between February and August 2015. Prescriptions of antimicrobials as SAP were compared with current SAP Guidelines, consolidated from a literature review, regarding 5 criteria—appropriate antimicrobial selection, dosing, timing of administration, redosing and duration of treatment. Results: We reviewed 224 charts, 112 from each hospital type. The majority ( P = 1.000) of patients received SAP when indicated (77.3% and 100.0%, respectively, from the teaching and private hospitals). A noteworthy 21.1% and 45.9% of patients received antimicrobials without an indication, respectively, from teaching and private hospitals. Compliance to all 5 of the criteria was not met by either hospital type. Overall, the teaching hospital met the most criteria (3 out of 5) in 58.8% of situations. Conclusions: Current SAP practices in South Africa's teaching and private hospitals diverge from current SAP Guidelines. Inappropriate overuse of SAP occurs in both hospital sectors, while underuse was found in the teaching hospital. Full compliance to the 5 criteria was not met by either hospital. Noncompliance was largely attributed to inappropriate selection and dosing. Quality improvement interventions, continued surveillance and local standardized evidence-based SAP Guidelines are needed to improve care. This is already happening.